2013
DOI: 10.3389/fpsyt.2012.00117
|View full text |Cite
|
Sign up to set email alerts
|

Yoga on Our Minds: A Systematic Review of Yoga for Neuropsychiatric Disorders

Abstract: Background: The demand for clinically efficacious, safe, patient acceptable, and cost-effective forms of treatment for mental illness is growing. Several studies have demonstrated benefit from yoga in specific psychiatric symptoms and a general sense of well-being.Objective: To systematically examine the evidence for efficacy of yoga in the treatment of selected major psychiatric disorders.Methods: Electronic searches of The Cochrane Central Register of Controlled Trials and the standard bibliographic database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
164
0
15

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(183 citation statements)
references
References 38 publications
(34 reference statements)
4
164
0
15
Order By: Relevance
“…Innen rusfeltet og psykisk helsevern er det sterkest evidens for effekten av yoga for depresjon (7,9,10). Det er noe svakere evidens for at yoga har effekt for angst og søvnforstyrrelser (9,10).…”
Section: Yoga Som Behandlingsformunclassified
See 1 more Smart Citation
“…Innen rusfeltet og psykisk helsevern er det sterkest evidens for effekten av yoga for depresjon (7,9,10). Det er noe svakere evidens for at yoga har effekt for angst og søvnforstyrrelser (9,10).…”
Section: Yoga Som Behandlingsformunclassified
“…To oppsummeringsartikler tyder også på at yoga har effekt som en komplementaer terapi for ADHD, schizofreni og rusmiddelproblemer (9,11).…”
Section: Yoga Som Behandlingsformunclassified
“…Many scholars have expounded on this topic before and discussed how yoga can be used as psychotherapeutic tool [6][7][8]19]. It is sufficient to say that ancient yoga literature has a plethora of techniques that can be harnessed to modern psychotherapeutic practice.…”
Section: Yoga Is About Exercising Mindmentioning
confidence: 99%
“…Against this background, it is not surprising that yoga is used as a part of psychotherapy [2,3] or sometimes even as a stand-alone psychotherapeutic tool [4,5]. Parallel to this inclusion in practice, literature is emerging to justify it [6][7][8]. Many would see this as a part of welcome natural progression in the evolution of modern yoga.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that, yoga has been used in an efficient manner in respiratory problems, cancer, rheumatoid arthritis, autism, depression, obesity, diabetes, kidney diseases, hemophilia and gastrointestinal disorders [ 14,15]. The effect of yoga on motor function, emotional state and cognitive function has been shown on adults along with children [16,17].…”
Section: Introductionmentioning
confidence: 99%